Relevance of autophagy markers to cytotoxicity of zinc compounds in macrophages. (June 2020) - Hirano, Seishiro; Kanno, Sanae
Abstract: Autophagy molecules such as microtubule-associated protein light chain 3 (LC3) and p62/SQSTM1 have been used as biomarkers of protective or conversely adverse effects of exposure to toxicants. In the present study we show changes in LC3-II (a lipidated form of LC3-I) and p62 levels in response to zinc compounds and some other toxicants in J774.1 murine macrophages. The cytotoxicity of either ZnO or ZnSO4 largely depended on the concentration of FBS or albumin in the culture medium. Accordingly, these authophagy markers were more remarkably increased when the cells were exposed to ZnO or ZnSO4 in the absence of FBS. We next addressed lysosomal function impairment and changes in LC3-II and p62 levels following exposure to TiO2, ZnO, and ZnSO4 . Lysosomal pH was quickly decreased by autolysosome inhibitors such as bafilomycin A1 and chloroquine, while TiO2, ZnO and ZnSO4 did not decrease lysosomal pH. However, the amounts of LC3-II and p62 and the LC3-II/LC3-I ratio were increased either by the lysosomal inhibitors and the Zn compounds. LC3-II and p62 levels were increased after exposure to arsenite and lipopolysaccharide (LPS). The p62 and phospho-p62 levels were also increased by either ZnSO4 and bafilomycin A1 in HEK293 cells stably expressing RFP-LC3. The current observations suggest that LC3-II and p62 levels were increased as consequences of early effects of toxicants without changing lysosomal pH. Graphical abstract: Unlabelled Image Highlights: Toxicity of ZnO and that of ZnSO4 were compatible in J774.1 cells. BSA and FBS significantly decreased toxicity of ZnO and ZnSO4 . Alkalinization of lysosoms increased LC3-II/LC3-I and p62. ZnO and ZnSO4 increased LC3-II/LC3-I and p62 without changing lysosomal pH. Increases in LC3-II/LC3-I and p62 are early signs of cell injury caused by toxicants.